Implementation of Fraud Risk Assessment To Mitigate The Fraud Risk in Tax Audit Process - Qomarudin Alfatah; Nicholas Agustinus L. Tobing (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
The emergence of a variety of fraud schemes, ineffective internal controls, and the number of fraud cases that occur in the taxation sector, encourage researches related to fraud risk assessment, especially in tax audit activities. This study aimed to identify potential fraud schemes risks, evaluate risk controls and discuss anti-fraud strategies using a case study at the Directorate General of Taxes in Indonesia. With a sequential mix method approach through a combination of quantitative and qualitative research, and by using rational choice theory, this research extends the literature of previous studies by providing evidence that fraud can be prevented by increasing the probability to detect fraud scheme. This study fills out the gaps related to fraud risk assessment research in the tax audit process which have been rarely performed in the literatures.The results concluded that of the 20 fraud scenarios identified, there were 7 fraud scenarios categorized as high level of residual fraud risk, 9 fraud scenarios at the medium level, and the rest at low levels. This study discussed appropriate controls to mitigate the residual fraud risk to be maintained at the level of organizational risk appetite. In addition, this study also discussed anti fraud strategies that are relevant to the organization, through evaluating anti-fraud strategies that have been previously implemented and anti-fraud strategies that have never been implemented